STUDI LAYANAN INFORMASI BERBASIS STIFIn UNTUK SISWA KELAS IX DI SMP IT ROBBANI BANJARBARU - Rahmadani, Rahmadani; Jarkawi, Jarkawi; Handayani, Eka Sri (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2019)
The teenage phase is a fairly critical phase so that every teenager needs a suitable environment so that later they are able to achieve achievements in the family, school and community. Based on this, an environment that is designed in the family, school and community is needed so that each individual can develop according to his potential. Although basically schools are not the only institution that forges students but schools have a considerable impact on the formation of an individual. Therefore, researchers are interested in implementing STIFIn-based Information Services with the aim of optimizing the potential of students. The method used in this study is qualitative. The subjects in this study were students of class IX Rabbani Banjarbaru IT Middle School. The sample in this study were 1 teacher, 2 students, and 2 studaents.The implementation stages of STIFIn-based Information Services for grade IX students at Rabbani Banjarbaru IT Middle School start from the process of exploring the needs of students after the explanation service of the results of the STIFIn-Based Personality Test, to adjust the needs of students then the information service content provided is STIFIn-based Learning Information Services.The results showed that not all information content could be understood, because there was the use of foreign languages and scientific terms that were not familiar to students. In addition, the results and explanation of STIFI-based personality tests are not fully recognized by students, this is due to the environmental factors that influence students in carrying out their developmental tasks.